2022
DOI: 10.3389/fpsyt.2022.930212
|View full text |Cite
|
Sign up to set email alerts
|

Differences of medically unexplained symptoms among patients of different ages and sexes in the psychological clinic of a general hospital and the influencing factors of MUS: A cross-sectional study

Abstract: ObjectiveTo analyse differences in sex, age, depression, insomnia, psychological stress, resilience, and perceived social support among patients with medically unexplained symptoms (MUS) in a psychological clinic of a general hospital, and to explore the influencing factors of MUS.MethodsThis is a cross-sectional study. Seven hundred forty-six first-time patients were assessed with the integrated psychosomatic comprehensive evaluation system (IPS) to evaluate their MUS, depression, insomnia, psychological stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…A cross-sectional study of different ages and psychological stress showed that the PHQ-9 and PSS-10 scores were higher in the middle age group (26–44 years old) than high age group (>45 years old). It is possible that males between the ages of 27 and 45 may experience heightened psychological stress than others ( 45 ). This study also showed that patients with epilepsy were more likely to develop depression within 1–5 years, which was inversely correlated with the duration of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study of different ages and psychological stress showed that the PHQ-9 and PSS-10 scores were higher in the middle age group (26–44 years old) than high age group (>45 years old). It is possible that males between the ages of 27 and 45 may experience heightened psychological stress than others ( 45 ). This study also showed that patients with epilepsy were more likely to develop depression within 1–5 years, which was inversely correlated with the duration of the disease.…”
Section: Discussionmentioning
confidence: 99%